Perancangan Aplikasi Kasir dan Inventory Persediaan Toko Buku dengan Metode SDLC (System Development Life Cycle) - Shandy Juniantoro; Fahira Galuh Pangestu (Journal Of Informatics And Busisnes, 2025)
In today's digital era, the need for efficient and integrated systems is increasing, including in the retail trade sector such as bookstores. With an application equipped with a cashier feature, bookstore operations can be more effective and efficient. This application not only helps in the sales transaction process, but also in the management of book data, stock, financial reports, and recording of sales activities in real time. To ensure that the application created can run properly according to its function, software testing is required. One of the commonly used testing methods is Blackbox Testing. This application is made using the SDLC method, System Development Life Cycle (SDLC). From the blackbox testing that has been carried out on the 5 existing menus, the results obtained are in accordance with what is expected, both in appearance and functionality of each button on the existing menu..